Hull design & stability analysis of solar boat / Nik Najmi Nik Min - Nik Min, Nik Najmi (2022)
For this project only focused on hull design and analysis stability of the boat. List a few hull designs and make a comparison to choose the best and suitable for my this project. After choosing hull design,do some rough sketching first on the paper. After confirming the shape and length of the boat,proceed in making line plan using PolyCAd. There are a few features in PolyCAD such as weight estimation, calculating hydrostatic force and analysis stability of the boat by generating through the drawing.